Supraspinal and Afferent Signaling Facilitate Spinal Sensorimotor Network Excitability After Discomplete Spinal Cord Injury: A Case Report - Militskova, Alena; Mukhametova, Elvira; Fatykhova, Elsa; Sharifullin, Safar; Cuellar, Carlos A.; Calvert, Jonathan S.; Grahn, Peter J.; Baltina, Tatiana; Lavrov, Igor (Frontiers in Neuroscience, 2020)
Objective: In this study we evaluated the role of residual supraspinal and afferent signaling and their convergence on the sublesional spinal network in subject diagnosed with complete paralysis (AIS-A). Methods: A combination of electrophysiologic techniques with positional changes and subject-driven reinforcement maneuvers was implemented in this study. Electrical stimulation was applied transcutaneously at the T9-L2 vertebra levels and the spinal cord motor evoked potentials (SEMP) were recorded from leg muscles. To test the influence of positional changes, the subject was placed in (i) supine, (ii) upright with partial body weight bearing (less than 30% body weight support), and (iii) vertically suspended without body weight bearing (100% body weight support) positions. Results: Increase in amplitude of SEMP was observed during transition from supine to upright position, supporting the role of sensory input in lumbosacral network excitability. Additionally, amplitudes of SEMP were facilitated during reinforcement maneuvers, indicating a supralesional influence on sub-lesional network. After initial assessment, subject underwent rehabilitation therapy with following electrophysiological testing that reviled facilitation of SEMP. Conclusions: These results demonstrate that combination of electrophysiological techniques with positional and reinforcement maneuvers can add to the diagnostics of discomplete SCI. These findings also support an idea that integration of supraspinal and afferent information on sub-lesional circuitry plays a critical role in facilitation of spinal sensorimotor network in discomplete SCI.